Is online and distance learning a viable option for teacher education? - Dobozy, Eva (IEEE, 2013)
Australia is in the grip of a teacher shortage. One way to assist in the supply of sufficient qualified school teachers is through the provision of initial teacher education (ITE) at a distance. Advancements in learning technologies are rapidly transforming distance-delivered ITE, enabling the reimagining and redesigning of open and distance learning (ODL). Unsurprisingly, the new and flexible teaching and learning provisions have increased the appeal of ITE through ODL and, as a consequence, Curtin University has experienced a great increase in enrolments in ITE courses delivered through open and distance modes. Nevertheless, little is known, as yet, about the learners who choose to enrol in ITE at Curtin University delivered fully online through either open or distance modes. The distinction is made between open (through Open Universities Australia) and distance (through Curtin University), because of the different entry requirements for ITE. This presentation reports on parts of a large, multi-university study investigating learning experiences of university students studying a variety of subjects in different modes. The research question was as follows: What are commencing students' characteristics, motivations concerns as they embark on their studies through ODL? The findings reported are from in-depth interviews with pre-service teachers who opted to enrol in ITE through open mode. The qualitative data analysis was informed by sociocultural theory, which has, as its primary tenet, the social construction of meaning. Sociocultural theory pays close attention to the importance of social, cultural and historic contexts and language to mediate the production of knowledge and insight and uncover unequal educational opportunities, based on social, cultural, and/or economic factors.